2017
DOI: 10.1177/2150131917705206
|View full text |Cite
|
Sign up to set email alerts
|

Which Fecal Immunochemical Test Should I Choose?

Abstract: Objectives: To summarize the fecal immunochemical tests (FITs) available in the United States, the 2014 pathology proficiency testing (PT) program FIT results, and the literature related to the test characteristics of FITs available in the United States to detect advanced adenomatous polyps (AAP) and/or colorectal cancer (CRC). Methods: Detailed review of the Food and Drug Administration’s Clinical Laboratory Improvement Amendments (CLIA) database of fecal occult blood tests, the 2014 FIT PT program results, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…The sample available in this study was small; future studies of larger representative samples are needed for confirmation and improved precision of estimates. In vitro spike‐in proficiency tests have demonstrated high sensitivity and specificity (all ≥93%) for hemoglobin in all three tests used in our study; however, such tightly controlled studies may not translate into similarly high‐performance characteristics in real‐world settings of variable sample preparation, handling, and analysis. Our analysis represents real‐world performance of the FITs that clinics chose to use, and results are intended to inform future FIT choices and the comparative cost‐effectiveness of each.…”
Section: Discussionmentioning
confidence: 99%
“…The sample available in this study was small; future studies of larger representative samples are needed for confirmation and improved precision of estimates. In vitro spike‐in proficiency tests have demonstrated high sensitivity and specificity (all ≥93%) for hemoglobin in all three tests used in our study; however, such tightly controlled studies may not translate into similarly high‐performance characteristics in real‐world settings of variable sample preparation, handling, and analysis. Our analysis represents real‐world performance of the FITs that clinics chose to use, and results are intended to inform future FIT choices and the comparative cost‐effectiveness of each.…”
Section: Discussionmentioning
confidence: 99%
“…However, most brands of FIT have limited evidence demonstrating their accuracy for detection of CRC. Daly et al found published data from colonoscopy‐confirmed studies of FIT performance for only 6 of the 26 versions of FIT sold in the United States . Because studies have shown variable performance of different FITs across studies in which individuals undergo multiple tests to compare outcomes, it should not be assumed that versions of FIT that lack published data have suitable performance characteristics …”
Section: Options For Crc Screeningmentioning
confidence: 99%
“…Daly et al found published data from colonoscopyconfirmed studies of FIT performance for only 6 of the 26 versions of FIT sold in the United States. 113 Because studies have shown variable performance of different FITs across studies in which individuals undergo multiple tests to compare outcomes, [114][115][116] it should not be assumed that versions of FIT that lack published data have suitable performance characteristics. 117 The original, low-sensitivity guaiac tests have largely been superseded by HSgFOBT and FIT in organized screening programs around the world, and a similar shift is underway in the United States.…”
Section: Stool-based Crc Screening Testsmentioning
confidence: 99%
“…Although there are a large number of qualitative 15 and qualitative 16 FIT available, it could be argued that the available evidence suggests that both qualitative and quantitative FIT appear to give somewhat similar clinical outcomes 10 and both could be used in assessment of patients presenting with lower abdominal symptoms if the disadvantages of the two rather different approaches were carefully kept in mind.…”
Section: Selecting a Faecal Immunochemical Testmentioning
confidence: 99%